2012
DOI: 10.4082/kjfm.2012.33.4.243
|View full text |Cite
|
Sign up to set email alerts
|

A Case of Scrub Typhus Complicated by Acute Calculous Cholecystitis

Abstract: We report a case of acute calculous cholecystitis through scrub typhus. A 69-year-old woman presented with a history of general myalgia, fever, and right abdominal pain. She referred to our hospital for surgical treatment of clinically suspected acute cholecystitis. Physicians concluded the cause of cholecystitis as gall bladder (GB) stone and proper antibiotics treatment of scrub typhus was started later. The patient developed acute respiratory distress syndrome and multi organ failure through scrub typhus. F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
8
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 15 publications
0
8
0
Order By: Relevance
“…No systematic studies have reported the treatment duration of complicated scrub typhus, with the exception of anecdotal reports (20)(21)(22). Although 10 to 14 days of antibiotics were used to treat complicated scrub typhus in several case reports, our study suggests that short-duration antibiotics are sufficient for treatment of complicated scrub typhus.…”
Section: Discussionmentioning
confidence: 72%
“…No systematic studies have reported the treatment duration of complicated scrub typhus, with the exception of anecdotal reports (20)(21)(22). Although 10 to 14 days of antibiotics were used to treat complicated scrub typhus in several case reports, our study suggests that short-duration antibiotics are sufficient for treatment of complicated scrub typhus.…”
Section: Discussionmentioning
confidence: 72%
“…In previous reports of scrub typhus with acute cholecystitis, most patients presented with upper abdominal pain, changes in aminotransferase levels, and wall enhancement and distension of the GB on CT, leading to suspicions of acute cholecystitis and considerations of surgical treatment. As these patients did not present with a typical eschar [ 2 3 5 7 ], physicians did not include scrub typhus in the differential diagnosis of cholecystitis.…”
Section: Discussionmentioning
confidence: 99%
“…The symptoms of this disease are usually mild and self-limited; however, it is sometimes accompanied by severe complications such as pneumonia, acute kidney injury (AKI), acute respiratory distress syndrome (ARDS), meningoencephalitis, shock, gastrointestinal bleeding, and myocarditis ( 2 3 4 5 6 7 8 ). Scrub typhus complicated by acute cholecystitis has been rarely reported, and the clinical course of this complication is not well understood ( 9 10 11 12 13 14 ). Herein, we conducted a retrospective study to investigate the characteristics of acute cholecystitis in patients with scrub typhus.…”
mentioning
confidence: 99%
“…A total of 1,733 reports were searched in PubMed (n=1,710) and website of The Korean Journal of Internal Medicine (n=23). A total of 7 subjects were identified as having scrub typhus complicated by acute cholecystitis ( 9 10 11 12 13 14 ).…”
mentioning
confidence: 99%
See 1 more Smart Citation